Forecasting of the population’s reproduction of Krasnodar region - A. A. Zhirova; D. A. Maksimov (Путеводитель предпринимателя, 2020)
Demographic forecasts are a base of modern social policy. The future of the Russian Federation depends on the reproduction of the population. The author considers the expected number and life expectancy of the population of the country’s third largest region.